Focal nodular hyperplasia of the liver in children after hematopoietic stem cell transplantation. (17th May 2013) - Masetti, Riccardo; Zama, Daniele; Gasperini, Pietro; Morello, William; Prete, Arcangelo; Colecchia, Antonio; Festi, Davide; Pession, Andrea
Abstract FNH is a non‐malignant neoplasia of the liver rarely described in children. A significant percentage of the pediatric cases have been reported in patients with a history of malignant disease treated with chemo‐radiation therapy and in children who were given HSCT. Little is known about the pathogenesis of FNH in transplanted children, but many risk factors linked to the HSCT procedure have been hypothesized. The detection of hepatic nodules, particularly in children who underwent HSCT for a previous malignancy, always raises a diagnostic dilemma. To help the physicians in the diagnostic management of this rare entity, we have retrospectively evaluated a series of transplanted children diagnosed with FNH in our Center over the last 15 yr. In this period, we found 10 new diagnoses of FNH. The diagnostic work‐up included CEUS, abdominal CT, and MRI. A liver biopsy was performed in two patients. The median FUP time after diagnosing FNH was 3.8 yr, with an abdominal US and no malignant transformation were observed. Possible risk factors and indications for the management of FNH in transplanted children are reported and discussed in a comprehensive review of the literature.